Compositional Changes in Cell Wall Polysaccharides from Five Sweet Cherry (Prunus avium L.) Cultivars during On-Tree Ripening - Basanta, Maria Florencia (2014)
Excessive softening is a major cause of postharvest deterioration during transportation and storage of fresh cherries. In continuing our studies to identify the factors determining the textural differences between sweet cherry fruit genotypes, we evaluated the solubilization, depolymerization, and monosaccharide composition of pectin and hemicelluloses from five sweet cherry cultivars (‘Chelan’, ‘Sumele’, ‘Brooks’, ‘Sunburst’, and ‘Regina’) with contrasting firmness and cracking susceptibility at two developmental stages (immature and ripe). In contrast to what is usually shown in most fruits, cherry softening could occur is some cultivars without marked increases in water-soluble pectin. Although polyuronide and hemicellulose depolymerization was observed in the water-soluble and dilute-alkali-soluble fractions, only moderate association occurs between initial polymer size and cultivar firmness. In all the genotypes the Na2CO3-soluble polysaccharides (NSF) represented the most abundant and dynamic wall fraction during ripening. Firm cultivars showed upon ripening a lower neutral sugars/uronic acid ratio in the NSF, suggesting that they have a lower proportion of highly branched polyuronides. The similar molar ratios of arabinose plus galactose to rhamnose [(Ara+Gal)/Rha] suggest that the cultivars differed in their relative proportion of homogalacturonan (HG) and rhamnogalacturonan I (RG-I) rather than in the size of the RG side chains; with greater proportions of HG in firmer cherries. Ultraviolet matrix-assisted laser desorption/ionization time-of-flight mass spectrometry was useful to identify the depolymerization patterns of weakly bound pectins, but gave less accurate results on ionically bound pectins, and was unable to find any pattern on covalently bound pectins.